The efficacy and adverse events of bevacizumab combined with temozolomide in the treatment of glioma: a systemic review and meta-analysis of randomized controlled trials - Wei, SiYao; Chang, LanYin; Zhong, Yi (Frontiers in Medicine, 2024)
OBJECTIVES: To assess the efficacy and adverse events of bevacizumab (BEV) combined with temozolomide (TMZ) in the treatment of glioma.Randomized controlled trials (RCT) involving BEV combined with TMZ in the treatment of glioma were searched using PubMed, Embase and Cochrane library, and a comprehensive meta-analysis was conducted. The primary outcomes were overall survival time (OS) and progression-free survival time (PFS), and the secondary outcome was adverse events. Researchers conducted literature screening, data extraction and quality assessment according to inclusion and exclusion criteria. RevMan 5.3 software was used for meta-analysis. RESULTS: A total of 8 prospective RCTs of 3039 cases were included in the metaanalysis. Meta-analysis showed that compared with TMZ alone, BEV combined with TMZ could significantly improve PFS, OS and complete remission rate (CR). A total of 6 studies reported related adverse events, mainly including thrombocytopenia, neutropenia, leukopenia, anemia and fatigue. Combination therapy may have more adverse events but no serious consequences. CONCLUSIONS: The combination of BEV and TMZ had a better therapeutic effect on glioblastoma, significantly prolonged the survival time of patients and improved the quality of life. However, some patients are afflicted with the adverse events of combination therapy, and subsequent studies should continue to conduct larger, multi-center RCTs to confirm the findings and explore in depth how to minimize and manage adverse events effectively.